Comparison of stochastic streamflow generators and the use thereof within the water resources yield model and MIKE Hydro Basin - Maass, Lourens Francois (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.